Toward Resilient and Peaceful Futures: Climate Security and Governance in the Global South - Muhammad Danish Mohd Haikel; Nur Izzah Hadirah Zawawi; Syahir Arif Syahmi Sazali (WIMAYA, 2025)
This study investigates the pivotal issues between climate change and security in the Global South. These countries, which often contribute the lowest emissions and are the least wealthy, are among those affected by climate change. This study aims to examine how governance challenges influence peacebuilding amid environmental crises by reform the security systems to incorporate climate security dimensions. Existing studies highlight the connection between environmental crises and conflict but often emphasize the Global North. There is a lack of comprehensive analysis exploring how good governance, diplomacy, and multilateral cooperation in the Global South can address climate security risks. The aim of this research is to fill that gap by examining governance approaches that will enhance peace and build more resilience amid environmental pressures. This study utilizes a mixed-methods approach, combining policy reviews, case studies from the Global South, and quantitative analysis of environmental and conflict data. The results were understood using themes and statistics. The research highlights that effective governance is characterized by transparency and diversity can reform climate resilience and reduce prolonged impact. Multilateral efforts that address Global South voices yield more sustainable pathways and peace outcomes. The form of “climate diplomacy” that focuses on local, community-based solutions offer alternatives to conventional securitized approaches. This supports the urgent call to frame climate security as a collaborative governance challenge. Its findings provide empirical evidence and practical policy for climate adaptation with peacebuilding and security strategies and sustainable governance in the Global South amidst ongoing environmental change.